2012
DOI: 10.1007/s00296-012-2582-2
|View full text |Cite
|
Sign up to set email alerts
|

Authorship problems in scholarly journals: considerations for authors, peer reviewers and editors

Abstract: Authorship problems in scholarly journals shake the foundations of research, diminish scientific quality of papers and devalue records of citation tracking services. The 'Publish or Perish' mantra is thought to drive some instances of unfair, honorary authorship, particularly in countries of emerging scientific power. Though causes of honorary, gift, guest and ghost authorship are still ill-defined, it is possible to avoid some of these instances by improving awareness of what constitutes authorship and by adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 35 publications
0
50
0
5
Order By: Relevance
“…In spite of this, authorship is seen as an underserved area of education in the responsible conduct of research [4,22]. To avoid inappropriate authorship, all those involved, research institutions, authors, editors and publishers, must understand the importance of fair crediting and take measures to ensure adherence to current guidelines and requirements [2,23]. It is, however, discouraging that an intervention study among medical students found that instruction about formal authorship criteria had no effect on students’ deciding about authorship dilemmas [24].…”
Section: Discussionmentioning
confidence: 99%
“…In spite of this, authorship is seen as an underserved area of education in the responsible conduct of research [4,22]. To avoid inappropriate authorship, all those involved, research institutions, authors, editors and publishers, must understand the importance of fair crediting and take measures to ensure adherence to current guidelines and requirements [2,23]. It is, however, discouraging that an intervention study among medical students found that instruction about formal authorship criteria had no effect on students’ deciding about authorship dilemmas [24].…”
Section: Discussionmentioning
confidence: 99%
“…While journals and professional societies have developed a number of approaches to contributorship issues (Rennie et al 2000;Gasparyan et al 2013;Baskin 2014), little research exists about the mechanisms that authors themselves use to address these problems.…”
Section: Introductionmentioning
confidence: 99%
“…In respected medical journals it is estimated at 21%, and that number may be much higher in less prominent journals and in certain countries [5] . In a self-reported study 33% of corresponding authors admitted to having honorary authors, and that the practice was found to be more common in Europe and Asia [6] .…”
mentioning
confidence: 99%